Interactions of selected gold(iii) complexes with DNA G quadruplexes. Issue 8 (3rd December 2014) - Gratteri, P.; Massai, L.; Michelucci, E.; Rigo, R.; Messori, L.; Cinellu, M. A.; Musetti, C.; Sissi, C.; Bazzicalupi, C.
Abstract : The interactions of three Au(iii ) complexes with human telomeric DNA sequences: Auoxo6 turned out to be very effective in inducing and binding the G-quadruplex DNA conformation. Abstract : The interactions of three representative gold(iii ) complexes with human telomeric DNA sequences were analysed using a variety of biophysical methods, including DNA melting, circular dichroism, SPR and ESI MS; remarkable interactions were highlighted for all tested complexes, although they were associated to significantly different binding profiles. The most interesting compound was Auoxo6, a dinuclear gold(iii ) complex, which beyond manifesting a conspicuous binding affinity for the G-quadruplex conformation, turned out to be very effective in inducing a non-canonical secondary structure. These findings may clear the way for novel biological and pharmacological applications of this class of metal compounds.